Cost-effectiveness analysis of stent type in endoscopic treatment of gastric leak after laparoscopic sleeve gastrectomy. Issue 5 (22nd February 2018) - Cosse, C; Rebibo, L; Brazier, F; Hakim, S; Delcenserie, R; Regimbeau, J M
Abstract: Background: Gastric leak is the most feared surgical postoperative complication after sleeve gastrectomy. An endoscopic procedure is usually required to treat the leak. No data are available on the cost-effectiveness of different stent types in this procedure. Methods: Between April 2005 and July 2016, patients with a confirmed gastric leak undergoing endoscopic treatment using a covered stent (CS) or double-pigtail stent (DPS) were included. The primary objective of the study was to assess overall costs of the stent types after primary sleeve gastrectomy. Secondary objectives were the cost-effectiveness of each stent type expressed as an incremental cost-effectiveness ratio (ICER); the incremental net benefit; the probability of efficiency, defined as the probability of being cost-effective at a threshold of €30 000, and identification of the key drivers of ICER derived from a multivariable analysis. Results: One hundred and twelve patients were enrolled. The overall mean costs of gastric leak were €22 470; the mean(s.d.) cost was €24 916(12 212) in the CS arm and €20 024(3352) in the DPS arm ( P = 0·018). DPS was more cost-effective than CS (ICER €4743 per endoscopic procedure avoided), with an incremental net benefit of €25 257 and a 27 per cent probability of efficiency. Key drivers of the ICER were the inpatient ward after diagnosis of gastric leak (surgery versus internal medicine), type of institution (private versus public) and duration of hospital stay per endoscopic procedure. Conclusion: DPS for the treatment of gastric leak is more cost-effective than CS and should be proposed as the standard regimen whenever possible. Abstract : Double pigtail is better